2021
DOI: 10.3390/jcm10184107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fatigue and Unrecognized Depression in Patients with Inflammatory Bowel Disease in Remission under Immunosuppressants and Biologicals

Abstract: Background: Although highly prevalent among inflammatory bowel disease (IBD) patients, fatigue remains an unmet clinical need. The aim was to describe the prevalence of fatigue in an IBD population in remission and identify factors associated with fatigue. Methods: IBD patients in clinical and biochemical remission under treatment with immunomodulators or biologicals were included. Fatigue, physical tiredness and depression were assessed using the fatigue Visual Analogue Scale (fVAS), the Shortened Fatigue Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Female sex is a well-known factor associated with fatigue [ 14 , 24 , 25 , 28 , 29 , 33 ]. Similar to general population, in our group of patients, fatigue was strongly associated with female sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female sex is a well-known factor associated with fatigue [ 14 , 24 , 25 , 28 , 29 , 33 ]. Similar to general population, in our group of patients, fatigue was strongly associated with female sex.…”
Section: Discussionmentioning
confidence: 99%
“…In the univariate analysis, t test, Chi-squared test and Fisher’s exact test were used to determine whether there were significant differences between patients presenting with fatigue and those without fatigue. Variables were selected taking into account the pre-existing data in the literature [ 6 , 10 , 11 , 14 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depression and fatigue have common behavioral, affective and cognitive characteristics; furthermore, they may even share similar causal pathways [ 7 , 46 , 51 ]. Truyens et al [ 52 ] suspected fatigue to be a symptom of underlying undetected depression. This hypothesis was supported by our study, in which 100% of patients with conspicuous values on the HADS-D scale had fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Severe IBD has been shown to impact psychology and is associated with new-onset depression [ 53 ]. Conversely, depression can negatively affect the course of IBD [ 52 , 54 – 56 ]. Hence identifying and appropriately addressing depression in patients with IBD are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…While one study identified disease chronicity as a factor contributing to fatigue ( 31 ) another study observed lower fatigue levels in patients with longer disease duration ( 97 ). Finally, one study showed no significant relationship between disease duration and fatigue ( 44 ).…”
Section: Factors Associated With Ibd-related Fatiguementioning
confidence: 99%